The Polarity Paradigm: Phenomenological and Psychoanalytical Insights into the Subject - Brudzińska, Jagna (B@belonline, 2020)
This article tends to connect phenomenological research with the psychoanalytical approach by focusing on the issue of conflict as the crucial dimension of human nature and its dynamics. On this basis, it becomes clear that human nature cannot be explained through a strict causal schema; rather, it can be grasped by exploring the dynamic motivational structures of experience which are expressed in the ambivalent tensions and striving tendencies of persons as subjects of the lifeworld. I stress that conflict is not a mere additional and accidental characteristic of experience that can somehow be eliminated, rather, it affects the fundamental structure of personal experience and should therefore be understood as a constitutive moment of human nature. Thereby, my claim is that both self-experience and the development of community can only be understood in the light of motivational conflicts.